Did the megafauna range to 4300 BP in South America? - Cione, Alberto Luis (2001)
A date of 4300 ± 90 BP for extinct megafauna in Argentina is discussed. The fossil remains come from the Guerrero Member (area) of the Luján Formation near the city of Luján, Buenos Aires Province. The age of the top of the Guerrero Member is constrained by more than 60 radiocarbon dates obtained from the overlying Río Salado Member of Luján Formation, Las Escobas Formation, and Puesto Callejón Viejo Soil, most of them older than 4300 BP. In view of its low collagen content, the 14C measurement of bone sample from Luján should not be accepted uncritically. Because of the poor bone preservation and the possible introduction of "young" contaminants that were not completely eliminated, the 14C date of 4300 ± 90 BP is not reliable. Both biostratigraphic and 14C dating evidence indicates that the date of 4300 BP for the last representative of extinct megafauna in South America is unsupported.